The Maternal Brain: An Organ with Peripartal Plasticity - Katharina Maria Hillerer; Volker Rudolf Jacobs; Thorsten Fischer; Ludwig Aigner (Neural Plasticity)
The time of pregnancy, birth, and lactation, is characterized by numerous specific alterations in several systems of the maternal body. Peripartum-associated changes in physiology and behavior, as well as their underlying molecular mechanisms, have been the focus of research since decades, but are still far from being entirely understood. Also, there is growing evidence that pregnancy and lactation are associated with a variety of alterations in neural plasticity, including adult neurogenesis, functional and structural synaptic plasticity, and dendritic remodeling in different brain regions. All of the mentioned changes are not only believed to be a prerequisite for the proper fetal and neonatal development, but moreover to be crucial for the physiological and mental health of the mother. The underlying mechanisms apparently need to be under tight control, since in cases of dysregulation, a certain percentage of women develop disorders like preeclampsia or postpartum mood and anxiety disorders during the course of pregnancy and lactation. This review describes common peripartum adaptations in physiology and behavior. Moreover, it concentrates on different forms of peripartum-associated plasticity including changes in neurogenesis and their possible underlying molecular mechanisms. Finally, consequences of malfunction in those systems are discussed.